Correlation between lean six sigma implementation, adoption readiness and SME performance in Malaysian manufacturing firms - Raidah, Rami Abdulhakeem Hasan Ba (2021)
Lean Six Sigma (LSS) is considered as the current trend method of Quality Management in large enterprises. Yet, its implementation in small and medium sized enterprises is still at an early stage. Small and medium companies have not received sufficient attention regarding the critical success factors (CSFs) to LSS implementation, however 98.5% business establishments in Malaysia are SMEs. Literature review supported that there is an agreement about the importance of CSFs to LSS implementation, yet there is no agreement about what constitutes these CSFs. Further, just few studies are considering the outcome of LSS in manufacturing SMEs performance. Moreover, very few publications to date have scientifically measured the readiness for LSS deployment in manufacturing SMEs context. Accordingly, a standard model for CSFs of LSS implementation is still lacking in the current literature related to SMEs. Recognizing the severe global competition encountering Malaysian market and the influential role of SMEs in enhancing Malaysian economy, there is a need to emphasize the ability of manufacturing SMEs in achieving perfection and excellence in all operational dimension including Quality Management. This study investigated the direct relationship between CSFs to LSS implementation and manufacturing SMEs performance. Furthermore, this study investigated the moderation role of adoption readiness on the direct relationship between CSFs to LSS implementation and manufacturing SMEs performance. The present study limited its scope within the context of Malaysian manufacturing SMEs. Survey-based method has used to collect data. As current literature lack of using an advance analysis method such as structural equation modeling, Variancebased SEM, which is known as SmartPLS method is applied in this study. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) have used to assess convergent validity, discriminate validity, unidimensionality, and to test the goodness of model fit and to test the hypotheses. This study found that top management commitment, supplier quality management, training and education, reward and recognition system, process audit are positively influence on manufacturing SMEs performance. However, linking LSS to SME strategy was found not effective on manufacturing SMEs performance. Moreover, the study found that the adoption readiness only moderates the direct relationship between top management commitment and manufacturing SMEs performance. Further, this research ended by developing a model for implementing LSS successfully in Malaysian manufacturing SMEs. The recommendations and implication also have provided in this research.